2023
DOI: 10.1039/d2qm01232d
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-inspired adhesive hydrogels for local immunomodulation

Abstract: The important function of the immune system is to protect the body from foreign pathogens and tumor cells, and to participate in the process of tissue repair and anti-tumor activity...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 185 publications
0
6
0
Order By: Relevance
“…Therefore, substantial efforts have been made to design inherent immunomodulatory hydrogels that can induce pro-regenerative macrophage polarization. [19][20][21][22] 3. Design of Hydrogels for Immunomodulation…”
Section: Immunomodulation Opportunities For Tissue Repair and Regener...mentioning
confidence: 99%
“…Therefore, substantial efforts have been made to design inherent immunomodulatory hydrogels that can induce pro-regenerative macrophage polarization. [19][20][21][22] 3. Design of Hydrogels for Immunomodulation…”
Section: Immunomodulation Opportunities For Tissue Repair and Regener...mentioning
confidence: 99%
“…However, many studies have successfully incorporated synthetic molecules which resemble the catechol structure of DOPA, [102][103][104] the abundant adhesive substance found in the mussel foot proteins, to fabricate tissue-adhesive hydrogels. [105][106][107] Some synthetic chemicals mimicking the polyol structure of mussel adhesives are dopamine (DA), tannic acid (TA), GA, caffeic acid, etc. For example, Montazerian et al developed a Gel-methacryloyl (GelMA)-DA-adhesive hydrogel via photo-cross-linking using different photo-initiators [108] (Figure 4G).…”
Section: Catechol Chemistrymentioning
confidence: 99%
“…It has been reported that catechol compounds play a role in the local immune response by virtue of their capacity to scavenge reactive oxygen species. [52][53][54] Collectively, the RAP patch acts as an inhibitor of inflammation in chronic wounds through its antimicrobial and anti-inflammatory properties, providing a promising therapeutic approach for the treatment of chronic inflammatory skin conditions.…”
Section: Proposed Mechanism Of Rap In Chronic Inflammatory Skin Suppr...mentioning
confidence: 99%